Determinan of Invesments Interest in Sharia Digital Mutual Funds Among Generation Z In Langsa City - Fahriansah; Ajran Nura; Khairatun Hisan; Farhah; Rahmat Mulia (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2024)
Generation Z faces a series of challenges, including limited financial resources, yet the demographic of investors in the Indonesian capital market is predominantly composed of Generation Z, including in Langsa City. This research aims to uncover determinants, including the influence of factors such as investment knowledge, celebrity endorsement, and word of mouth, on the investment interest of Generation Z in Langsa City in Shariah digital mutual funds. This study employs quantitative research methods, collecting data through a questionnaire with a sample of 110 respondents and analyzing it using the SPSS application with multiple linear regression. The t-test results indicate that the investment knowledge factor has a t-value of 5,894, surpassing the t-table value 1.659, with a significance level of 0.000 ≤ alpha 0,05, thus accepting H1. The t-value for the celebrity endorsement factor is 3,705, exceeding the t-table value of 1.659, with a significance level of 0,000 ≤ alpha 0,05, accepting H2. The t-value for word of mouth is -0,269, surpassing the t-table value of 1.659, with a significance level of 0,788 ≤ alpha 0,05, rejecting H3. Therefore, the results of this study indicate that investment knowledge and celebrity endorsement significantly influence the investment interest of Generation Z in Langsa City in Shariah digital mutual funds. At the same time, word of mouth does not significantly impact.